Monocyte Subsets in Schistosomiasis Patients with Periportal Fibrosis. (13th March 2014) - Fernandes, Jamille Souza; Araujo, Maria Ilma; Lopes, Diego Mota; Souza, Robson da Paixão de; Carvalho, Edgar M.; Cardoso, Luciana Santos
Abstract : A major issue with Schistosoma mansoni infection is the development of periportal fibrosis, which is predominantly caused by the host immune response to egg antigens. Experimental studies have pointed to the participation of monocytes in the pathogenesis of liver fibrosis. The aim of this study was to characterize the subsets of monocytes in individuals with different degrees of periportal fibrosis secondary to schistosomiasis. Monocytes were classified into classical (CD14 ++ CD16 − ), intermediate (CD14 ++ CD16 + ), and nonclassical (CD14 + CD16 ++ ). The expressions of monocyte markers and cytokines were assessed using flow cytometry. The frequency of classical monocytes was higher than the other subsets. The expression of HLA-DR, IL-6, TNF- α, and TGF- β was higher in monocytes from individuals with moderate to severe fibrosis as compared to other groups. Although no differences were observed in receptors expression (IL-4R and IL-10R) between groups of patients, the expression of IL-12 was lower in monocytes from individuals with moderate to severe fibrosis, suggesting a protective role of this cytokine in the development of fibrosis. Our data support the hypothesis that the three different monocyte populations participate in the immunopathogenesis of periportal fibrosis, since they express high levels of proinflammatory and profibrotic cytokines and low levels of regulatory markers.